Pros and Cons of Mentioning Islam in Indonesia and Indonesian Islam - Utari Marcela; Dartim (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This article discusses cultural acculturation in life, especially in the aspect of definition and socio-cultural identity. One of the issues that will be discussed is culture related to the multiculturalism perspective of Islam in Indonesia. The problem includes how to distinguish the concept of Islam in Indonesia and Indonesian Islam where this article will show that socio-cultural modality is the main force of Islam in Indonesia including religion that has an attachment to socio-cultural adaptation. The socio-cultural process gave birth to several cultural aspects including literary works, local songs (tembang), and also building art (architecture). Based on these examples, it can be said that there is adaptation among Muslims with the culture in Indonesia. In general, the opinion of religion and its adaptation occurs for every Muslim in a global context and experience